A 15‐Year Content Analysis of Three Qualitative Research Traditions. (8th March 2019) - Flynn, Stephen V.; Korcuska, James S.; Brady, Nicole V.; Hays, Danica G.
Abstract : The authors conducted a qualitative content analysis on the consistency, rigor, and methodological identity of 83 phenomenological ( n = 44), grounded theory ( n = 25), and consensual qualitative research ( n = 14) articles published between 2002 and 2016. The results indicate a distinct pattern of qualitative research practices in professional counseling.